Mabel Walker Willebrandt papers - Willebrandt, Mabel Walker, 1889-1963.
Correspondence, speeches, writings, family papers, and printed matter relating primarily to Willebrandt's service as U.S. assistant attorney general under Presidents Warren G. Harding and Calvin Coolidge. Correspondence includes letters to Willebrandt's parents and pertains chiefly to social and political life in Washington, her efforts as an enforcer of the 18th Amendment to the U.S. Constitution, Republican Party politics, and the issue and role of women in politics. Also includes a file concerning the 1888 Haystack Massacre, Stevens County, Kan.
Lawyer and public official.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Coolidge, Calvin, -- 1872-1933.; Harding, Warren G. -- 1865-1923.; Walker family; Willebrandt family; United States; United States. -- Office of the Assistant Attorney General; Republican Party (U.S. : 1854- ); Prohibition; Women -- Political activity; Stevens County (Kan.) -- History; United States -- Politics and government -- 1919-1933.; Washington (D.C.) -- Social life and customs; Lawyers; Public officials